K units of the K8 and K54 capsular polysaccharides produced by Acinetobacter baumannii BAL 097 and RCH52 have the same structure but contain different di-N-acyl derivatives of legionaminic acid and are linked differently. (1st September 2019) - Arbatsky, Nikolay P.; Kenyon, Johanna J.; Kasimova, Anastasiya A.; Shashkov, Alexander S.; Shneider, Mikhail M.; Popova, Anastasiya V.; Knirel, Yuriy A.; Hall, Ruth M.
Abstract: The K8 and K54 capsular polysaccharides were isolated from Acinetobacter baumannii BAL 097 and RCH52, respectively, and studied by sugar analysis, partial acid hydrolysis and selective solvolysis with CF3 CO2 H in the presence of 2-methyl-1-propanol, along with 1D and 2D 1 H and 13 C NMR spectroscopy. The following structures of related branched tetrasaccharide repeats (K units) of the polysaccharides were established:Image 2 where Leg indicates 5, 7-diamino-3, 5, 7, 9-tetradeoxy-d -glycero- d -galacto -non-2-ulosonic (legionaminic) acid and R indicates ( R )-3-hydroxybutanoyl or acetyl in the ratio 2.5:1. The sequences of the KL8 and KL54 capsule gene clusters were closely related. The difference in the acyl group at O-7 on the sidechain legionaminic acid is due to differences in two genes in the legionaminic acid biosynthesis cluster. The wzy genes encoding the K unit polymerases are also different and make different linkages between the K units, allowing the first sugar of both K units to be identified asd -Glc p NAc. The shared Gtr20 glycosyltransferase, also encoded in KL63, forms the α-l -Fuc p NAc-(1 → 3)-d -Glc p NAc linkage, and Gtr19 was predicted to form α-d -Gal p NAc-(1 → 3)-l -Fuc p NAc. Gtr18 from KL8 is 75% identical to Gtr108 from KL54 and both would link the Leg derivative tod -Gal p NAc. Hence the genes present at the K locus were consistent with the composition and structures of the K8 and K54 capsular polysaccharides. Graphical abstract: Image 1 Highlights: Capsule structures were obtained for Acinetobacter baumannii clinical isolates carrying KL8 and KL54. Capsule structures are related, differing in the presence of a non-2-ulosonic acid and linkage between units. The function of the glycosyltransferases, Wzy polymerases and initiating transferase were unambiguously assigned.